The Role of Competency and Interpersonal Communication In Improving Performance - Novalien Carolina Lewaherilla; Asiani Sijabat (Quantitative Economics and Management Studies, 2022)
This study aims to examine and analyze the effect of competence and interpersonal communication on the performance of PKB employees of the Maluku Province BKKBN Representatives. This type of research is a quantitative research, using a questionnaire as a research instrument. The sample selection technique used simple random sampling. The population of this research is the PKB representative of the Maluku Province BKKBN, totaling 100 employees with a total sample of 50 employees. The results of the study stated that competence and interpersonal communication partially or simultaneously had a positive and significant influence on the performance of PKB employees of the Maluku Province BKKBN Representatives. The variable of competence and interpersonal communication explains the variable of employee performance by 78.2%, this means that competence and interpersonal communication are two factors that must be considered